Operando lab-on-fiber platform for concurrent monitoring of moisture degradation and lead leakage in perovskite solar cells - Binyun Xia; Weijin Chen; Junjun Jin; Zhengyang Ke; Jiahong Cheng; Xiaoyu Huang; Yanbo Nie; Qidong Tai; Ning Wang (Chemical Engineering Journal, 2026)

Divergent responses of soil methane uptake to nitrogen addition across upland ecosystems - Xinya Sui; Hong Zhang; Yunyi Xie; Yaqi Liu; Xiaoli Cheng; Guihua Liu; Junjun Wu (Soil and Tillage Research, 2026)

Retraction notice to “High daytime abundance of primary organic aerosols over Mt. Emei, Southwest China in summer” [Sci. Total Environ. 703 (2020) 134475] - Yue Zhao; Hong Ren; Junjun Deng; Linjie Li; Wei Hu; Lujie Ren; Siyao Yue; Yanbing Fan; Libin Wu; Jie Li; Yele Sun; Zifa Wang; et al. (Science of The Total Environment, 2026)

Warm-season non-refractory PM2.5 composition in urban Tianjin and Beijing: Two megacities of the North China Plain - Qingqing Wang; Lu Lei; Yanpei Li; Wei Hu; Libin Wu; Junjun Deng; Jin Feng; Chun Chen; Borong Cheng; Jiang Zhu; Pingqing Fu; Yele Sun; et al. (Journal of Environmental Sciences, 2026)

Immune efficacy evaluation of a PEDV spike protein-derived multi-epitope subunit vaccine candidate in mice - Yihong Luo; Miaozhan Wei; Bin Wang; Huaping Yin; Xiaojiang Guo; Taotao Ji; Fei Xu; Junjun Ban; Zehong Cen; Bijun Zhou; Chunlan Shan; Anchun Cheng; et al. (Veterinary Immunology and Immunopathology, 2026)

Stage-specific ion release from dual-crosslinked alginate/boron-doped bioactive glass hydrogel accelerates infected wound healing - Fuqiang Song; Linyuan Jiang; Anqi Ye; Rong Huang; Anwen Lai; Longyang Xu; Wei Shen; Junjun Li; Jiayan Hui; Andi Suo; Yanzhi Xiong; Xiaoyu Dong; et al. (Carbohydrate Polymers, 2026)

Role of flow electrode chamber channel depth in charge transfer and ion migration in FCDI: Mechanistic insights and energy efficiency evaluation - Cheng Wang; Jianrui Niu; Situ Mu; Yongkun Shi; Jing Zhang; Chun Liu; Junjun Ma (Chemical Engineering Journal, 2026)

Benign solidification of molten slag on rotary cup atomizer: slag shell formation, remelting and residue characteristics - Yiwen Lv; Maolin Dai; Junjun Wu; Hong Wang; Yudong Ding; Min Cheng; Xun Zhu; Qiang Liao (Waste Management, 2026)

Genetic and transcriptomic identification of WPG1 controlling nitrogen allocation-related leaf chlorisis and premature senescence in wheat - Haili Zhang; Li’ao Zhang; Qiang Li; Ling Yi; Juanyu Zhang; Yanyan Tang; Jinhui Wang; Junjun Liang; Tao Li; Fangyan Zhang; Yiran Cheng; Yi Wang; et al. (Theoretical and Applied Genetics, 2026)

Elucidating the mechanism of sulfur reactions over NiFe2O4 oxygen carrier at atomic level - Cheng Shen; Yu Li; Daifen Chen; Xin Liu; Junjun Sun; Jintian He; Laihong Shen (Fuel, 2025)

Corrigendum to “Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration” [Chem. Eng. J. Volume 523 (2025) 168846] - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Experimental and simulation study of volatile organic compounds adsorption over natural Opoka based zeolite 13X - Yangyu Liu; Chenxi Zhang; Arman Peyravi; Lei Jiang; Zaher Hashisho; Linghe Cheng; Hailong Zhang; Zhongzheng Yang; Junjun Wang; Jiuyue Wang; Yuping Tong (Chemical Engineering Journal, 2025)

Involvement of nitric oxide-mediated cytosolic glucose-6-phosphate dehydrogenase in soybean resistance to heavy metal toxicity - Junjun Huang; Luyu Wang; Ziyu Jia; Kunxia Cheng; Rongzhi Han; Juanjuan Yu; Huahua Wang (Plant Cell Reports, 2025)

Melatonin improves aluminum tolerance in soybean through modification of cell wall and vacuolar compartmentalization of aluminum - Huanan Li; Ziyu Jia; Kunxia Cheng; Luyu Wang; Junjun Huang; Huahua Wang (Journal of Plant Physiology, 2025)

Ionic covalent organic framework engineered super-charged thin-film composite polyamide membrane for desalination - Hui Wang; Rui Ding; Tao Wu; Xianjuan Zhang; Lijuan Cheng; Kai Xu; Yu Zheng; Xiao Pang; Genliang Ji; Liqiang Shen; Junjun Li; Runnan Zhang; et al. (Chemical Engineering Journal, 2025)

Insights from Computational Fluid Dynamics and In Vitro Studies for Stent Protrusion in Iliac Vein: How Far Shall We Go? - Zhenmin Fan; Jian Lu; Hao Cheng; Xia Ye; Xiaoyan Deng; Pengfei Zhao; Junjun Liu; Mingyuan Liu (Cardiovascular Engineering and Technology, 2025)

Ecosystem-atmosphere exchange of methane in global upland and wetland ecosystems - Junjun Wu; Hong Zhang; Xiaoli Cheng; Guihua Liu (Agricultural and Forest Meteorology, 2025)

Fish community dynamics following the low-head dam removal and newly installed fish passage in a headstream tributary of Jinsha River, Southwest China - Junjun Tan; Junjian Sun; Yuanyang Wang; Huiwu Tian; Bixin Cheng; Jie Qing; Xin Yan; Gan Sun; Senfan Ke; Giri Raj Kattel; Xiaotao Shi (Science of The Total Environment, 2024)

Highly efficient adventitious root regeneration and Agrobacterium rhizogenes-mediated hairy root transformation in pear - Cheng Xue; Liyan Chang; Junjun Liu; Kaidi Gu; Pengfei Zheng; Jun Wu (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Two genes encoding a bacterial-type ABC transporter function in aluminum tolerance in soybean - Junjun Huang; Huanan Li; Yiwei Chen; Xiaoyu Li; Ziyu Jia; Kunxia Cheng; Luyu Wang; Huahua Wang (Plant Cell Reports, 2024)

Triboelectric signal enhancement via interface structural design and integrated with deep learning for real-time online material recognition - Cheng Shen; Jingyi Chen; Yue Liu; Zhenming Chen; Junjun Huang (Chemical Engineering Journal, 2024)

Thermally-stable and flame-retardant metal-organic framework-based separator for high-performance lithium-ion batteries - Wen Ren; Jiang Liang; Meng Huang; Wei Qian; Ming Zhao; Fan Qiao; Lianmeng Cui; Zixin Zhang; Junjun Wang; Cheng Zhou; Zhe Wang; Qinyou An; et al. (Chemical Engineering Journal, 2024)

Soil methane uptake is tightly linked to carbon dioxide emission in global upland ecosystems - Junjun Wu; Long Chen; Hong Zhang; Xiaoxiang Zhao; Xiaoli Cheng; Kerong Zhang; Guihua Liu (Agriculture, Ecosystems & Environment, 2024)

Depth control analysis of Smartfloat using sea trail data and parameter identification - Ping Cheng; Junjun Cao; Jialuan Xiao; Yiming Zhong; Caoyang Yu (Ocean Engineering, 2024)

Multi-chamber membrane capacitive deionization coupled with peroxymonosulfate to achieve simultaneous removal of tetracycline and peroxymonosulfate reaction byproducts - Minghao Yu; Chenxu Yang; Meng Chen; Yunke Li; Kexin Kang; Cheng Wang; Jianrui Niu; Situ Mu; Jing Zhang; Chun Liu; Junjun Ma (Journal of Hazardous Materials, 2024)

Dynamic analysis and simulations of a deep-sea floating mining vehicle multi-body system under real-world operating conditions - Jialuan Xiao; Ping Cheng; Junjun Cao; Rui Lin; Mengzhi Luo; Caoyang Yu; Baoheng Yao; Yongli Hu (Ocean Engineering, 2024)

An observational prospective study based on a large cohort of HIV-negative neurosyphilis patients with particular reference to the Jarisch-Herxheimer reaction - Rui-Rui Peng; Juan Wu; Wei Zhao; Lin Zhu; Zhifang Guan; Xin Gu; Mei Shi; Junjun Yu; Yanchun Cheng; Pingyu Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The purpose of this study is to outline a complete picture of Jarisch-Herxheimer reaction (JHR) in the central nervous system among HIV-negative neurosyphilis patients. Methods A prospective study cohort of 772 cases with almost all stages of neurosyphilis depicted the features of JHR including occurrence rate, risk profiles, clinical manifestations, medical management and prognosis. Results The total occurrence rate of JHR was 9.3% (95% CI, 7.3-11.4%), including 4.1% (95% CI, 2.7-5.6%) with severe JHR. The reaction started 5 h after treatment initiation, peaked after 8 h, and subsided after 18 h. Patients with severe JHR experienced a longer recovery time (26 h). Patients with general paresis (OR = 6.825), ocular syphilis (OR = 3.974), pleocytosis (OR = 2.426), or a high CSF-VDRL titre (per log 2 titre increase, OR = 2.235) were more likely to experience JHR. Patients with general paresis had an 11.759-fold increased risk of severe JHR. Worsening symptoms included cognitive impairment, mania, nonsense speech, and dysphoria, while symptoms of hallucination, urination disorder, seizures, myoclonus, or aphasia appeared as new-onset symptoms. Neurosyphilis treatment did not need to be interrupted in most patients with JHR and could be reinstated in patients with seizures under supportive medication when JHR subsided. Conclusion Severe JHR displayed a 4.1% occurrence rate and clinicians should pay particular attention to patients at a higher risk of JHR. The neurosyphilis treatment regime can be restarted under intensive observation for patients with severe JHR and, if necessary, supportive medication should be initiated and continued until the end of therapy.

Application of microbially induced calcium carbonate precipitation (MICP) process in concrete self-healing and environmental restoration to facilitate carbon neutrality: a critical review - Junjun Chang; Dongyang Yang; Cheng Lu; Zhitao Shu; Shengjiong Deng; Liwei Tan; Shaoqing Wen; Ke Huang; Pengchang Duan (Environmental Science and Pollution Research, 2024)

Phosphate-solubilizing bacteria improve the antioxidant enzyme activity of Potamogeton crispus L. and enhance the remediation effect on Cd-contaminated sediment - Yuxin Cheng; Junjun Yuan; Gongting Wang; Zhenzhen Hu; Wenqing Luo; Xin Zhao; Yali Guo; Xiaonan Ji; Wei Hu; Min Li (Journal of Hazardous Materials, 2024)

Tree stem methane emissions: Global patterns and controlling factors - Junjun Wu; Hong Zhang; Xiaoli Cheng; Guihua Liu (Agricultural and Forest Meteorology, 2024)

Catalytic activation of persulfate by nanoscale zero-valent iron-derived supported boron-doped porous carbon for bisphenol A degradation - Fuxiang Du; Xiaowei Huo; Chao Xue; Chenggui Zhang; Huichao Wang; Chao Dai; Yang Yang; Cheng Lai; Junjun He (Environmental Science and Pollution Research, 2024)

Performance enhancement of ice storage capsules by biomimetic fins - Liangyu Wu; Jie Yu; Junjun Yang; Wei Gao; Chengbin Zhang; Cheng Yu (International Journal of Refrigeration, 2024)

Small molecule linoleic acid inhibiting whey syneresis via interact with milk proteins in the fermentation of set yogurt fortified with c9,t11-conjugated linoleic acid - Junjun Qing; Cheng Peng; Hongbing Chen; Haixing Li; Xiaohua Liu (Food Chemistry, 2023)

Stabilizing Cr(Ⅲ) deriving from tannery sludge with kaolin and organic matter - Junjun Ma; Tao E; Shuyi Yang; Liang Chen; Ying Cheng; Jia Yu; Yun Li (Environmental Research, 2023)

Biofilm formation and development during the pyrite bioleaching of moderately thermophilic microorganisms - Li Shen; Jinju Cheng; Junjun Wang; Yejuan Zhang; Hao Zhou; Xueling Wu; Jiaokun Li; Weiming Zeng (Hydrometallurgy, 2023)

High contribution of new particle formation to ultrafine particles in four seasons in an urban atmosphere in south China - Li Tao; Zhen Zhou; Jun Tao; Leiming Zhang; Cheng Wu; Jiawei Li; Dingli Yue; Zhijun Wu; Zhisheng Zhang; Ziyang Yuan; Junjun Huang; Boguang Wang (Science of The Total Environment, 2023)

Particulate organic carbon is more sensitive to nitrogen addition than mineral-associated organic carbon: A meta-analysis - Junjun Wu; Hong Zhang; Yongtai Pan; Xiaoli Cheng; Kerong Zhang; Guihua Liu (Soil and Tillage Research, 2023)

Changes in soil organic carbon stability in association with microbial carbon use efficiency following 40 years of afforestation - Qianxi Li; Wei Jia; Junjun Wu; Lingling Wang; Feng Huang; Xiaoli Cheng (CATENA, 2023)

Inversion of TEM measurement data via a quantum particle swarm optimization algorithm with the elite opposition-based learning strategy - Junjun Jiao; Jiulong Cheng; Yuben Liu; Haiyan Yang; Dingrui Tan; Peng Cheng; Yuqi Zhang; Chenglin Jiang; Zhi Chen (Computers & Geosciences, 2023)

Lattice stain dominated hydrazine oxidation reaction in single-metal-element nanosheet - Jie Shi; Qintao Sun; Wenxiang Zhu; Tao Cheng; Fan Liao; Mengjie Ma; Junjun Yang; Hao Yang; Zhenglong Fan; Mingwang Shao (Chemical Engineering Journal, 2023)

Recombinant HBsAg-S and RFRP-3 DNA vaccine promotes reproduction hormone secretion in sheep - Yi Ding; Xunping Jiang; Haijing Jing; Guiqiong Liu; Junjun Cheng (Theriogenology, 2023)

Nitrogen addition stimulates litter decomposition rate: From the perspective of the combined effect of soil environment and litter quality - Junjun Wu; Hong Zhang; Xiaoli Cheng; Guihua Liu (Soil Biology and Biochemistry, 2023)

Bioimmobilization and transformation of chromium and cadmium in the fungi-microalgae symbiotic system - Junjun Wang; Qinghua Tian; Linlin Cui; Jinju Cheng; Hao Zhou; Yejuan Zhang; Anan Peng; Li Shen (Journal of Hazardous Materials, 2023)

Association between plasminogen activator inhibitor-1 gene polymorphisms and susceptibility to Parkinson’s disease in Chinese patients - Qi Xu; Qilun Lai; Junjun Wang; Liying Zhuang; Lin Cheng; Yejia Mo; Lu Liu; Zexian Zhao; Ying Zhang; Shiting Weng; Song Qiao (Acta Neurologica Belgica, 2022)

How does the urban–rural income gap affect regional environmental pollution?——Re-examination based on the experience of cities at prefecture level and above in China - Weiwei He; Junjun Hou; Keke Cheng (Environmental Science and Pollution Research, 2022)

Identifying Carbon-Degrading Enzyme Activities in Association with Soil Organic Carbon Accumulation Under Land-Use Changes - Junjun Wu; Xiaoli Cheng; Yiqi Luo; Wenzhi Liu; Guihua Liu (Ecosystems, 2022)

Distinctive Roles of Wnt Signaling in Chondrogenic Differentiation of BMSCs under Coupling of Pressure and Platelet-Rich Fibrin - Baixiang Cheng; Fan Feng; Fan Shi; Jinmei Huang; Songbai Zhang; Yue Quan; Teng Tu; Yanli Liu; Junjun Wang; Ying Zhao; Min Zhang (Tissue Engineering and Regenerative Medicine, 2022)

Fine detection on water abundance of sandstone by joint inversion of seismic and CSAMT: a case study in the western Ordos Basin, China - Yi Dong; Jiulong Cheng; Laifu Wen; Peng Cheng; Fei Li; Junjun Jiao; Qisong Huang (Acta Geophysica, 2022)

Swimming behaviour of silver carp ( Hypophthalmichthys molitrix ) in response to turbulent flow induced by a D ‐cylinder - Senfan Ke; Zhiying Tu; Elsa Goerig; Junjun Tan; Bixin Cheng; Zhimin Li; Xiaotao Shi (Journal of Fish Biology, 2022)
Turbulence is a complex hydraulic phenomenon which commonly occurs in natural streams and fishways. Riverine fish are subjected to heterogeneous flow velocities and turbulence, which may affect their movements and ability to pass the fishways. However, studies focusing on fish response to turbulent flows are lacking for many species. Here we investigate the effects of the turbulence created by a vertical half‐cylinder of various diameters (1.9, 2.5, 3.2 and 5.0 cm) on the swimming ability and behaviour of silver carp, Hypophthalmichthys molitrix . The large D‐cylinders (3.0 and 5.0 cm) create specific vorticity and reduced velocities areas in their vicinity, which favours flow refuging behaviours (FRBs) and thus increased relative critical swimming speeds ( U rcrit , BL/s) of silver carp, by comparison to free‐flow conditions and cylinders of smaller diameter (1.9 and 2.5 cm). The flow speed at which silver carp maximized FRBs such as Karman gaiting downstream of the cylinder, holding position in the bow wake or entraining on the side ranged from 40 to 70 cm s −1 , depending on fish body size. When holding station near a cylinder under optimal flow speeds, the distance between the fish and the cylinder is related to the size of the fish, but also to the size of the cylinder and the produced vortices. The optimal holding region in the drag wake of the cylinder ranged from 28 to 40 cm downstream of the centre of the cylinder, depending on the size of the fish. Smaller fish, however, tend to use the reduced velocities areas located in the bow wake of the large cylinders. We hypothesize that fish will display FRBs, including maintaining a Karman gait in turbulent flow, when the ratio of the cylinder diameter to their body length is between 1:3 and 1:4. They also match their tail beat frequency to the vortex shedding frequency of the cylinder. Our results provide a better understanding of how silver carp respond to turbulent flows around physical structures, with implications for the design of nature‐like fishways or exclusion devices in both its native and invasive ranges.

Joint Inversion and Application of DC and Full-Domain TEM with Particle Swarm Optimization - Yi Dong; Jiulong Cheng; Haijun Xie; Fei Li; Junjie Xue; Laifu Wen; Zhi Chen; Junjun Jiao (Pure and Applied Geophysics, 2022)

Genetic control and phenotypic characterization of panicle architecture and grain yield-related traits in foxtail millet (Setaria italica) - Hui Zhi; Qiang He; Sha Tang; Junjun Yang; Wei Zhang; Huifang Liu; Yanchao Jia; Guanqing Jia; Aiying Zhang; Yuhui Li; Erhu Guo; Ming Gao; et al. (Theoretical and Applied Genetics, 2021)

How do Biotic and Abiotic Factors Regulate Soil Enzyme Activities at Plot and Microplot Scales Under Afforestation? - Qianxi Li; Ji Chen; Jiao Feng; Junjun Wu; Qian Zhang; Wei Jia; Qiaoling Lin; Xiaoli Cheng (Ecosystems, 2020)

Asymmetric response of soil methane uptake rate to land degradation and restoration: Data synthesis - Junjun Wu; Qiong Chen; Wei Jia; Chunyan Long; Wenzhi Liu; Guihua Liu; Xiaoli Cheng (Global Change Biology, 2020)
Land degradation and restoration profoundly affect soil CH 4 uptake capacity in terrestrial ecosystems. However, a comprehensive assessment of the response of soil CH 4 uptake to land degradation and restoration at global scale is not available. Here, we present a global meta‐analysis with a database of 228 observations from 83 studies to investigate the effects of land degradation and restoration on the capacity of soil CH 4 uptake. We found that land degradation significantly decreased the capacity of soil CH 4 uptake, except the conversion of pasture to cropland where the soil CH 4 uptake rate showed no response. In contrast, all types of land restoration significantly increased the capacity of soil CH 4 uptake. Interestingly, the response of soil CH 4 uptake rate to land degradation and restoration was asymmetric: the increased soil CH 4 uptake rate in response to the land restoration was smaller compared to the decrease in CH 4 uptake rate induced by the land degradation. The effect of land degradation on soil CH 4 uptake rate was not dependent on the time since land use change, but the CH 4 sink strength increased with the time since land restoration. The response of soil CH 4 uptake rate to both land degradation and restoration was predominantly regulated by changes in the soil water‐filled pore space, soil bulk density, and pH, whereas alterations in the substrate quantity and quality had negligible effect. Additionally, the effects of land degradation and restoration on soil CH 4 uptake were strongly related to the mean annual precipitation and soil texture. Overall, our results provide novel insights for understanding of how land degradation and restoration can affect the CH 4 sink strength of upland soils, and more importantly, our findings are beneficial to take measures to enhance the potential of soil CH 4 uptake in response to global land use change.

Contrasting soil C and N dynamics inferred from δ13C and δ15N values along a climatic gradient in southern China - Jiao Feng; Fan Yang; Junjun Wu; Qiong Chen; Qian Zhang; Xiaoli Cheng (Plant and Soil, 2020)

Soil labile and recalcitrant carbon and nitrogen dynamics in relation to functional vegetation groups along precipitation gradients in secondary grasslands of South China - Adugna Feyissa; Fan Yang; Jiao Feng; Junjun Wu; Qiong Chen; Xiaoli Cheng (Environmental Science and Pollution Research, 2020)

Attribution assessment and projection of natural runoff change in the Yellow River Basin of China - Zhe Yuan; Denghua Yan; Zhiyong Yang; Jijun Xu; Junjun Huo; Yanlai Zhou; Cheng Zhang (Mitigation and Adaptation Strategies for Global Change, 2018)

Paleogene lacustrine dolomitization, Xingou region, southern Qianjiang Depression, China - Junjun Shen; Bo Chen; Fangfang Chen; Chao Cheng; Yangfan Li; Ying Tian (Geosciences Journal, 2016)

Molecular cloning and characterization of a tropinone reductase from Dendrobium nobile Lindl - Wei Chen; Xiaofei Cheng; Zhenhua Zhou; Junjun Liu; Huizhong Wang (Molecular Biology Reports, 2013)